Influence of seeding time on yield of six irrigated rice cultivars - Infeld, José Alceu; Júnior, Paulo Silveira; Zonta, Elio Paulo (Pesquisa Agropecuaria Brasileira, 2014)
In order to verify the influence of seeding time and cultivar on yield or rice Oryza sativa L., the cultivars Bluebelle, Lebonnet, EEA 406, IRGA 408, BR-IRGA 409 and BR-IRGA 410 were sown at six different times from October 1st to December 15th during the growing seasons of 1978, 1979, 1980 and 1981. The average yield of BR-IRGA 410 (5,420 kg/ha) was significantly higher than the other cultivars, whereas the yield of BR-IRGA 409 (5,010 kg/ha) and IRGA 408 (4,970 kg/ha) was significantly higher than EEA 406 (4,590 kg/ha), Bluebelle 4,450 kg/ha) and Lebonnet (4,340 kg/ha). According to the curve adjustment of average yields of the different seeding times, the date of November 1st was responsible for the maximum production, and the interval ranging from October 16 to November 16 as the best for rice seeding in the southern part of the State of Rio Grande do Sul, Brazil.